ANALISIS PARATE EKSEKUSI OBYEK HAK TANGGUNGAN DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) YOGYAKARTA - , M Nur Cholis Moslim ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis aims to examine and analyze the implementation of parate execution under Article 6 UUHT The State Property Office and Auction Yogyakarta, ranging from procedures, and compliance with UUHT. This study is thus requires normative data material library research and field research. Data used in this study are secondary data, the legal regulations governing the implementation of parate execution, by linking empirical data, data obtained directly from the field. The results of the study were analyzed by descriptive qualitative. The results showed that 1). Implementation of parate execution in Yogyakarta KPKNL under Article 6 does not require the fiat / court orders and any sale by auction of mortgage objects through KPKNL, must submit a written request in writing to the Head of the auction KPKNL, accompanied by tender requirements documents, and in APHT must be agreed that the holder the first mortgage over the right to sell its own power if the debtor breach of contract, but if the lender is a bank, even if the debtor has been declared in default, then to resolve problem loans there are two strategies are pursued: a). Non Litigation is through negotiations again by Rescheduling, Reconditioning / business by changing the way most / all the conditions (requirements) that was originally agreed upon, and Recstructing / change the composition of the underlying loan financing. b). Litigation is based on the title executorial and can also be based on Article 6 UUHT (parate execution).